Utilization of health care in an African urban area: results from a household survey in Ouagadougou, Burkina Faso - Develay, Aude; Sauerborn, Rainer; Diesfeld, Hans J. (Social science & medicine, 1996)
This study analysed the level of utilization of different kinds of health care providers, and its correlates, by people reporting an illness via a household health survey in a representative sample of 547 households (3667 persons) in the city of Ouagadougou, Burkina-Faso in 1989. More than one-fourth of the sample reported suffering from a health care problem in the 2-week period preceding the interview. Self care was the most frequently reported type of care received (55.6%). Bivariate analysis and logistic regression revealed that the principal determinants of the utilization of modern care givers were age, socio-economic level, illness characteristics (type, length, severity), and cost of care and transportation. In particular, we found that: (1) Even though the family remained the main provider of care in case of minor (mild and short) illnesses, it did not prevent modern health facilities from playing their curative role in case of serious illnesses. (2) Residential zone (central versus peripheral zone) was not significantly associated with health care choice, which was contrary to expectation. (3) On the other hand, socio-economic status strongly affected health-seeking behavior. (4) The travel pattern of the ill persons favored health care facilities in the central zone. Taken together, the results of this study question the role of community health workers in the urban program of community health care which was in the process of being implemented at the time of the study. They suggest that the family, instead of the community health workers, should be seen as the provider of curative care for minor illnesses. Community health workers may have a more effective role in health education than in curative tasks.
Elektronische Reproduktion der Druck-Ausgabe 26. Februar 1999
Gesehen am 23.10.2024
Keywords: Burkina Faso